Effect of in ovo injection of various vitamins on Hatchability and embryo mortalities during embryogenesis stages of Japanese quails Coturnix japonica - Jaafur, Kussy M.; Kati, Salah M.; Shawkat, Tarki F. (Journal of Kerbala for Agricultural Sciences, 2016)
This study was conducted during at 4/3/2014 to 22/3/2014 in AL-Chiflawy hatchery ,ALmahawel – Babylon province to investigate the effected of injection of Japanese quail eggs by fat soluable vitamins , A,D3,E and AD3E on hatchability weight and length of hatched chicks , embryo mortality during embryogenesis .A total of 720 fertile eggs were used , eggs were distributed into 6 treatments each treatment included 120 eggs , each treatment included 3 replicated treatment were as follow: T1: negative control Treatment . T2: positive control Treatment it included injection of 50 microliter / egg with cor oil . T3: included injection of 50 microliter / egg of vit A (100 IU/egg) T4: included injection of 50 microliter / egg of vit E (15 IU/egg) T5: included injection of 50 microliter / egg of vit D3 (100IU/egg) T6: included injection of 50 microliter / egg of vit AD3E (100IU/egg) . Results revealed a significant surpassing (P<0.05) of vitamins injection (3th ,4th , 5th and 6th) on control treatment (1st and 2nd) in hatchability of fertile eggs , weight of hatched chick , there was no significant differences between treatment in length of chicks , but there was a significant effect of fat soluble vitamins on weight of dead embryo with a significant decrease of early , middle and late chick mortalities and the total mortalities as compared with the control treatment ,it was concluded that there is a positive role of fat soluable vitamins in improvement of hatchability , increase of weight of dead embryo , weight of hatched chicks with a decrease of embryo mortalities during embryogenesis .